An unusual case of nasal foreign body presenting as recurrent otitis media (Indian Journal of Case Reports, 2024)
Otitis media (OM) is a common problem involving children. In the majority, the cause is related to dysfunction of the Eustachian tube due to bacterial or viral rhinitis and less commonly due to nasopharyngeal tumors. We present a case of recurrent OM which was evaluated and incidentally found a nasal foreign body for which the patient was asymptomatic. This nasal body was the cause of recurrent OM which is very unusual.